2017
DOI: 10.1017/laq.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Tayza, Capital of the Petén Itzas: Teasing Meanings From Postclassic Pottery Styles

Abstract: A decade of public-works excavations on Flores Island—once Tayza, capital of the powerful Itza Maya confederacy in Postclassic- and contact-period Petén, Guatemala—has recovered large quantities of artifacts but without proper provenience controls. This important center is poorly understood in archaeological terms because of the dense modern construction that precludes systematic investigation. Thus, these excavated materials become critical despite their limitations for insights into the Itza settlement. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Above was approximately 25 centimeters of fill (plaza construction), which was initially dated to the Early Postclassic. Subsequent excavations in Itza territory, however, revealed that many decorative diagnostics of Late Postclassic pottery are rare outside of Tayza/Flores (Rice 2017; e.g., Ixlu; Rice and Rice 2016), and we now consider the plaza to actually date to this later period. This fill was also capped by thin plaster surfacing (Floor 2).…”
Section: Structure 719mentioning
confidence: 73%
“…Above was approximately 25 centimeters of fill (plaza construction), which was initially dated to the Early Postclassic. Subsequent excavations in Itza territory, however, revealed that many decorative diagnostics of Late Postclassic pottery are rare outside of Tayza/Flores (Rice 2017; e.g., Ixlu; Rice and Rice 2016), and we now consider the plaza to actually date to this later period. This fill was also capped by thin plaster surfacing (Floor 2).…”
Section: Structure 719mentioning
confidence: 73%